β-Lactam-Synthon-Interceded Metal/Acid-Free Diastereoselective Access to Highly Functionalized Oxazol-5-ones and Dihydroimidazoles - Singh, Amandeep; Shalini; Kaur, Harleen; Sharma, Palak; Anand, Amit; Kumar, Vipan (Synlett, 2017)
Facile diastereoselective access to functionalized oxazol-5-ones and dihydroimidazoles was accomplished through base-promoted intramolecular amidolysis and methoxide-assisted tandem intramolecular amidolysis/ring opening/intramolecular cyclization, respectively, of C-3-functionalized azetidin-2-ones.
Keywords: azetidinones; oxazolones; dihydroimidazoles; amidolysis; diastereoselectivity; tandem reaction